Treatment of Achlya Infection in Freshwater Seabass, Lates calcarifer (Bloch 1790) - Lau, Lik Ming; Kishio, Hatai (Asian Fisheries Society, 2017)
Achlya infection is a common disease in freshwater-reared fishes. A strain of water mould, Achlya sp. IPMB 1403, was isolated from the tail fin of dying freshwater-reared Asian seabass, Lates calcarifer (Bloch 1790) fry and was used in the present study for treatment trials. The antifungal effects of seawater and sodium chloride on hyphal growth and zoospore germination were investigated at 25 ºC by using seawater up to 30 ppt and NaCl up to 3.0 %. Seawater at 15 ppt and above and NaCl at 1.5 % and above inhibited hyphal growth, while exposure to seawater at 30 ppt for 2 h or NaCl at 2.0 % for 2 h or 3.0 % for 30 min was effective in killing both vegetative and zoosporic stages of the fungal strain. Toxicity tests were conducted using Asian seabass and Nile tilapia, Oreochromis niloticus (Linnaeus 1758) fry with the same treatment levels of seawater and NaCl for up to 2 h and mortality was recorded at 24 h. No mortality was observed in any of the Asian seabass fry groups, but 100 % mortality was observed for Nile tilapia fry in 3.0 % NaCl for 1 and 2 h treatments. Use of seawater and NaCl in aquaculture was effective for controlling a pathogenic Achlya sp. strain, but toxicity to the target aquaculture species needs to be assessed to determine a treatment concentration and duration that would ensure effectiveness as a fungicide as well as to minimise toxicity to the fish fry.